Quem somos nós, descendentes? Da história à socialização na constituição de identidades teuto-brasileiras - Portugueis, Diane (2013)
This paper addresses the establishment of the identities of German descendents in Brazil, specifically in the Southern and Southeastern regions. The relevance of this study arose from the vast influence of German descendents in Brazil, which is more visible in the cultural and economic dimensions of the country. It was noticed that there was a lack of studies addressing this population, both in terms of identity and cultural studies, as well as those related to social psychology in relation to their socialization in the globalized world. The method used was Oral History, namely life stories. The analysis of 6 stories made it possible for us to note the differences between two groups: descendents 20 to 30 years of age and those who are older, aged 50 to 60 years old. For the younger population, we pointed out to the recovery of their supposed identity in connection to identity policies mediated by the Germanness, and that was more evident for those who had not lived in Germany. For the older descendents, we noted a close connection with cultural hybridism (H. BHABHA, 2001), which was understood as the search to complement elements of both cultures (Brazil and Germany), and which added to the critical ownership that they make of traditions, as well as their own reinvention in the place where they live to the point that political identities are biasedly revealed